Telesna aktivnost med nosečnostjo in pojavnost carskega reza - Špegel, Urška (Obzornik zdravstvene nege, 2023)
Introduction: The incidence of cesarean section deliveries is increasing both nationally and globally. Compared to vaginal birth, cesarean sections are associated with a higher risk of complications. Physical activity during pregnancy has been shown to benefit both the mother and newborn and improve birth outcomes. The review aims to investigate the impact of physical activity during pregnancy on the incidence of cesarean section.Methods: A systematic literature review was conducted in the PubMed, SAGE, and Web of Science databases using English-language keywords. The search was limited to randomised trials published between 2012 and 2022. A flowchart was used to illustrate the search, review, and selection process. A critical evaluation of the articles and content analysis of the data were performed.Results: Out of 703 articles initially identified, 12 studies were included in the analysis. The results indicate that physical activity during pregnancy can contribute to reducing the incidence of cesarean section. Pregnant women are recommended to engage in 30 to 60 minutes of moderate physical activity two to four times a week.Discussion and conclusion: The findings of this review suggest that physical activity during pregnancy can reduce the incidence of cesarean section. Health professionals should encourage and motivate healthy pregnant women to engage in regular (assisted) physical activity.
Keywords: birth; fizična aktivnost; nosečnica; physical activity; porod; pregnant woman